Solar cooling system by absorption in areas of high irradiation in Colombia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper examines the potential of a solar refrigeration system by absorption in areas of high irradiation in Colombia for the conservation of food and medicine, through the analysis of Servel refrigeration characterized by a Domestic RH 131 refrigerator. For this analysis, real data was taken from the operation of the equipment, with input and output temperatures of each element of the system, in order to verify its cooling capacity. In this way, the working conditions were determined, as well as the heat required by the generator in which the chemical compression of the substance used to determine the solar collector will take place. For the simulation, the system is assembled in Trnsys coupled to thermal collectors and photovoltaic panels to simulate the real conditions of this, thus seeking to make an analysis of the behavior of the equipment and determine the viability of the system supported by solar energy